PENGARUH EFEKTIVITAS KOMUNIKASI, LINGKUNGAN SEKOLAH, DAN KOMITE SEKOLAH TERHADAP UPAYA PENINGKATAN MUTU PENDIDIKAN MENURUT PERSEPSI GURU DI SEKOLAH LUAR BIASA (SLB) KABUPATEN BANTUL (JURNAL ILMIAH TUT WURI HANDAYANI, 2013)
The Influence of Communication Effectivity, School Environment, and School Committe on Effort to Education Quality Improvement according to the Teachers Perception of the Special School in Bantul Regency.This research is intended to find out the effectivity influence of communication, school inveronment and school committe involved simultaneously on effort to education quality improvement at Special School, Bantul Regency. To find out the influence of communication efectivity on effort to education quality improvement at the Special School, Bantul Regency. The influence of school environment on effort to education quality improvement at the Special School, Bantul Regency.The influence of the school committe on effort to education quality improvement at the Special School, Bantul Regency. The population of this research were all the teachers of Special School Bantul which totally 292 teachers. The sample was 161 teachers it was taken from Isaac and Michael formula. In collection the data, the researcher used quota proportionate random sampling. The collection of the data of this research used questionnaire. The analysis technique used multiple regression and partial correlation with level significantly is 5 %. The result of the research showed that the effectivity of communication, school environment and school committe have positive influence and significant simultaneously on effort to education quality improvement at the Special School, Bantul Regency.Theeffective contribution effectivity of communication, school environment, and school committe on effort to education quality improvement is 21.3 %, thus the number 78.7% cannot be explained at this research caused by another factor. The effectivity of communication gave relative contribution is 45.31%, school environment gave relative contribution is 33.86% and school committe gave 20.83%.Whereas, the number of effective contribution to each free variable at the bound is 21.3%. The number effectivity of communication variable is 9.7%,the number of school environment variable is 7.2% and the number of school committe is 4.4%.The effectivity of communication had positiveinfluenced and significant on effort to education quality improvement at the Special School, Bantul Regency.The school environment had positive influenced and significant on effort to education quality improvement at the Special School, Bantul Regency. School committe had not influenced significantly on effort to education quality improvement at the Special School, Bantul Regency.